Ploning pag-ibig, paghihintay at pag-asa - Santos, Judy Ann; Garcia, Dante Nico; Lingan, Benjamin; Sebastian, Jourdan; Gonzales, Guia (Panoramanila Pictures, 2008)
Ploning, is a story of one man's search for the enigmatic woman, who has deeply wounded him in the past. Having grown up in an illegal Taiwanese fishing vessel, Rodrigo, 30 years old, returns to the beautiful island of Cuyo and is given from sunrise to look for his "Ploning". In his search, he discovers that the woman he loved and adored as a boy is not the woman he thought he knew. Ploning has displayed her maternal love for Digo, the 6 years old Rodrigo, but is shrouded in her mysterious love and devotion for Tomas, her childhood sweetheart who left her when she was 16. This 30-year-old spinster who has held a special place amongst, a devoted friends, a caring sister and a loving maternal figure is slowly unveiled through Rodrigo's memory and an emotional meeting with Ploning's confindante, Seling. Through his search, Ploning will be revealed as the island's most bittersweet source of selfless love.